Pendidikan Gizi Pencegahan Obesitas pada Remaja di SMP PK Al Kautsar Kartasura - Siti Zulaekah; Pramudya Kurnia; Mutalazimah Mutalazimah; Zulia Setiyaningrum (Jurnal Abdimas Kesehatan (JAK), 2023)
Obesity is a health problem that can occur in various circles, including adolescents. The prevalence of obesity in adolescents continues to increase, although various efforts have been made to prevent and control obesity. Health education with the lecture method is less effective to be applied to today's youth. Therefore, one of the educational methods provided is the provision of education through animated videos that can attract the attention of teenagers so that messages can be conveyed and increase adolescent knowledge. This educational activity will be held in September 2022 in the PK Al Kautsar Kartasura Junior High School Hall. The participants of this activity were 51 teenagers consisting of grades 8 and 9. Nutrition education began with giving a pretest, then continued with the provision of material containing indicators of obesity, causes, impacts and how to prevent obesity with animated video media, to see the increase in knowledge, students were given posttest and discussion and question and answer. Increased knowledge about anemia that occurred in 40 adolescents, while 11 adolescents did not experience an increase. The average increase in knowledge is 29.67 points. This increase in knowledge shows that providing education by presenting animated videos can be effective in increasing adolescent knowledge. Therefore, the parties suggest that similar activities can be carried out regularly to increase their knowledge of the health of their students.